The Effect of Financial Ratios on Profitability of Consumer Goods Listed on the IDX in 2015-2019 - Manurung, Yanti Lorenza; Atmoko, Alfriadi Dwi (Universitas Tidar, 2021)
This study aims to examine and obtain empirical evidence of the Effect of Financial Ratios on Profitability in Consumer Goods Industrial Sector Companies Listed on the Indonesia Stock Exchange in 2015-2019. The analytical method used is descriptive analysis, Classical Assumption Test, and Hypothesis Testing with IBM SPSS Statistics 23. The test results show that partially Current Ratio (CR), Total Assets Turn Over (TATO), Price Earning Ratio (PER) have a negative effect on Return On Assets (ROA). Debt to Equity Ratio (DER) has a positive and insignificant effect on Return On Assets (ROA), Debt Ratio (DR) has a negative and insignificant effect on Return On Assets (ROA), Fixed Charge Coverage (FCC) has a positive effect on Return On Assets (ROA), Simultaneously Current Ratio (CR), Debt to Equity Ratio (DER), Debt Ratio (DR), Total Assets Turn Over (TATO), Fixed Charge Coverage (FCC), Price Earning Ratio (PER) affect Return On Assets (ROA)